Changes on Serum Troponin T Level before and after Taking Standard Therapy Medication in Heart Failure Patients - Indrawijaya, Yen Yen Ari; Suharjono, Suharjono; Aminuddin, Muhammad; Retnowati, Endang; Rahman, Gilang Mauladi (Folia Medica Indonesiana, 2020)
Patients with advanced heart failure (NYHA FC III and IV heart failure) had positive cardiac troponin levels in previous cohort studies. In heart failure, cardiac troponin T (cTnT) is a biomarker that is sensitive to myocardial damage, especially myocardial necrosis. However, there is still little information regarding changes in cTnT levels during standard therapy. This prospective observational study is aimed at evaluating changes in cTnT levels before and after theadministration of standard therapy and evaluating symptom improvement before and after the administration of standard therapy in patients with severe heart failure. Measurement of cTnT levels and symptom improvement parameters before treatment was carried out on the first day of the inpatient and measurement after therapy was carried out on the last day of the inpatient. Sampling was done by consecutive sampling and found 30 patients in the inpatient room of the SMF Cardiovascular Disease, Dr. Soetomo Hospital, Surabaya during the months of May-July 2017. The results of the study obtained the average cTnT levels before therapy 33.48 + 31.88 pg/ml and the average cTnT levels after therapy 46.32 + 52.68 pg/ml. Based on the statistical difference test with the Wilcoxon sign-ranked test, there was no significant change in cTnT levels (p = 0.318). On the parameter of clinical symptom improvement, there was a significant decrease in pulse, respiratory rate, blood pressure, and mean arterial pressure before and after administration of therapy (p <0.05). There was no change in troponin T levels before and after the administration of therapy meant there was no worsening of myocardial necrosis.